The Study of Electrical Activity of the Triceps Brachia Muscle according to the Chemical Changes of Water Loss during Spike in Volleyball - Haythem Ali Alsayigh (Journal of Global Pharma Technology, 2017)
The aim of this study is to study muscle activity of triceps according to what happens from chemical changes due to loss of water in a volleyball game, especially in spike skill, since this skill requires the performance of high accuracy and speed of a big reaction. Was selected sample of players who suffer from potassium deficiency (Hypokalemia) as a result of incorrect nutrition and not to drink fluids regularly as well as the performance of the game in hot weather, which led to an imbalance in the ionic balance of the cell as a result lost a little amount of potassium ion is essential for the occurrence of muscle contraction. The results showed that continued positive performance without compensation potassium element led to an imbalance in muscular activity of the triceps muscle.Keywords: Electrical activity, Muscle triceps brachial, Chemical changes, Water loss, Spike and volleyball.